Vesicoureteral reflux and continuous prophylactic antibiotics - Lee, Ted (Investig Clin Urol, 2017)
Vesicoureteral reflux (VUR) management must be tailored based on the risk for further infections and renal scarring, gender, likelihood of spontaneous resolution, and parental preferences. Because we now understand that sterile VUR is benign and most reflux spontaneously resolves over time, the initial approach in majority of children is non-surgical with continuous antibiotic prophylaxis (CAP) and correction of bladder and bowel dysfunction. Despite increasing utilization of CAP over the past four decades, the efficacy of antibiotic prophylaxis has been questioned due to conflicting results of studies plagued with design flaws and inadequate subject sample size. The Randomized Intervention for Children with Vesicoureteral Reflux (RIVUR) trial, which was designed to address many of the limitations from previous studies, provided much needed answers. In this review, we sought to describe the controversy surrounding VUR management, highlight the results of RIVUR trial, and discuss how the RIVUR findings impact our understanding of CAP in the management of VUR.